2018
DOI: 10.1016/j.jbiotec.2018.06.345
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic features defining industrial relevant Lactococcus lactis, L. cremoris and L. lactis biovar. diacetylactis strains

Abstract: Lactococcus lactis strains constitute one of the most important starter cultures for cheese production. In this study, a genome-wide analysis was performed including 68 available genomes of L. lactis group strains showing the existence of two species (L. lactis and L. cremoris) and two biovars (L. lactis biovar. diacetylactis and L. cremoris biovar. lactis). The proposed classification scheme revealed coherency among phenotypic (through in silico and in vivo bacterial function profiling), phylogenomic (through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
5
1
Order By: Relevance
“…In the L. lactis biovar. diacetylactis CRL264 strain, citrate transport, and metabolism are composed of the chromosomal citM(ψcitO)-I-CDEFXG cluster [34]. However, in the present study, we only observed the cluster of citM(H)-CDEFGT(X) without citI gene.…”
Section: Resultscontrasting
confidence: 74%
“…In the L. lactis biovar. diacetylactis CRL264 strain, citrate transport, and metabolism are composed of the chromosomal citM(ψcitO)-I-CDEFXG cluster [34]. However, in the present study, we only observed the cluster of citM(H)-CDEFGT(X) without citI gene.…”
Section: Resultscontrasting
confidence: 74%
“…The citP gene is highly valued as a molecular marker of this biovar. But the plasmid encoding CitP is sometimes missing while the chromosomal cluster citDEFXG is highly conserved among the strains that produce diacetyl (Passerini et al, 2013;Torres Manno et al, 2018). For that reason, the citD chromosomal gene encoding the citrate lyase was chosen as target to highlight the diacetylactis biovar.…”
Section: Discussionmentioning
confidence: 99%
“…Before the advent of molecular methods for strain identification, these subspecies were identified using phenotypic tests (Schleifer et al, 1985). Later, several studies based on genome-wide (Kelleher et al, 2017;Torres Manno et al, 2018) and comparative analysis of ANI parameters (Cavanagh et al, 2015a) support the idea that these two subspecies can be considered as two distinct species lactis and cremoris. The use of this new denomination is now well admitted.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Lactococcus lactis isolates from dairy environment greatly differ in their genes from environmental strains [49], showing domestication of strains. As a consequence, their phenotype reflects their adaptation to a specific niche [50,51]. Similar exploitation of genomic data, through comparative genomics, have been performed with L. plantarum and Fructobacillus spp.…”
Section: Overviewmentioning
confidence: 99%